Plant protection in the wetlands of Kolkheti Lowland - O. Kharaishvili; Tinatin Gogishvili; L. Baidauri; Tinatin Darsavelidze; S. Zalishvili; P. Lortkipanidze; L. Toklikishvili; N. Sukhishvili; L.Giorgaze (Progress in Science, 2025)
The conceptual vision of our future academic activities is to use important innovations in the field of plant protection on a global scale. In particular, the development of environmentally safe measures against pests on wetlands is at the forefront. On dried wetlands, pests cause great damage, both in terms of crop reduction and deterioration of quality. Depending on the type of plant damage, there are specialized and omnivorous pests that damage various plant organs. Basically , highly toxic chemical pesticides of various groups are used against pests all over the world, including the swampy Kolkheti lowland, which have many negative characteristics: pollute the environment, soil, air, water. They decrease the number of beneficial organisms to a minimum. Therefore, chemical means should be used only in cases of extreme necessity. Plant protection measures should be used in cases where the number of pests exceeds the economic limit of harmfulness. Our vision consists the inclusion of new laboratory-developed, less toxic drugs in plant protection systems and the establishment of optimal regulations for their use.